An Overview on the Techniques of Soil Stabilization (International Journal of Innovative Research in Computer Science & Technology, 2020)
The main difficulty is still determining the  appropriate soil stabilizers to overcome the challenges  posed by soft soils, not only in terms of achieving the  required soil engineering features but also in terms of cost  and environmental effect. The purpose of this paper was to  look at the soil stabilization technologies that had been  created via experiments. The effectiveness of hydroxide  solution additive, fly ash terpolymeric cement, various  ashes, and cementitious binders for soil stabilizers were all  examined. Based on compressive strengths (UCS) or  California Bearing Ratio (CBR) tests, the performance of  these materials for supporting soft soils was determined  purely in terms of strength. These chemicals significantly  increased the strength of the soft ground, indicating that  they may be used as effective soil stabilizers in the field
Keywords: California Bearing Ratio (CBR); Soil; Soil stabilizer; Soil stabilization; Unconfined Compressive Strength (UCS)